PENGARUH RASIO KESEHATAN BANK TERHADAP PENYALURAN KREDIT MODAL KERJA PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI MASA PANDEMI COVID-19 - Veronica Amalia, Maike (Contemporary Studies in Economic, Finance and Banking, 2022)
Banking as an intermediary institution whose task is to collect funds from the community and channel it back to the community in the form of credit. In distributing credit, there are internal bank factors such as bank health that must be considered, which can be seen from several ratios such as CAR, LDR, NPM, BOPO, ROA, and NPL. This study aims to examine the effect of banking health ratios on the distribution of working capital loans to MSMEs during the Covid-19 pandemic. The object of this research is banking which is included in the list of BUKU for the period 2019-2021. The research sample used was 15 banking companies. This type of research is explanatory research with quantitative research methods. Based on the results of the study, it was shown that during the study period the CAR variable, LDR had a significant positive effect and NPL had a significant negative effect on the distribution of working capital loans to MSMEs. Meanwhile, simultaneously, all variables have a significant effect on the distribution of working capital loans to MSMEs with a magnitude of effect of 0.994106 or 99.41%. Some banking ratios are still in a stable condition even though the economy is weakening due to the pandemic, this is a strategic step for the government and banks, one of which is to maintain the quality of lending.